Images in Juan José Millás’ Photocolumns. A Study of People, Shots, and Textual Anchoring - Cárdenas Rica, María Luisa; Martín Ramallal, Pablo (Área Abierta. Revista de comunicación audiovisual y publicitaria, 2026)
This research examines the photocolumn as a vanguardist opinion journalism genre characterized by its inherent hybridity between image and text. The study focuses on the specific case of the “La Imagen” section in the supplement El País Semanal, authored by Juan José Millás, a renowned writer and journalist known for creating the articuento (a hybrid of a literary short story and a journalistic article). The methodology employed is a quantitative and qualitative content analysis, utilizing an originally designed analytical matrix to investigate the selection and treatment of the images. The findings demonstrate Millás’ strong commitment to the human element, consistently prioritizing people over locations and inanimate objects. Analysis of the photographic shots highlights a clear interest in visualizing the informative “who”, their action, and immediate context. Finally, the study confirms the crucial role of textual anchoring: the accompanying text does not merely complement the image but actively interprets it, imbuing it with new meaning. This discursive mechanism solidifies the photocolumn as an essential tool for providing the reader with other eyes to see reality.